Integrating regions : Asia in comparative context - Kahler, Miles, 1949-; MacIntyre, Andrew J., 1960- (Stanford University Press, 2013)
Asian regional institutions have proliferated in the new century. An investigation and explanation of institutional variation across regions contributes to an assessment of Asia's regional institutions. The determinants of choice for supranational regional institutions in Europe are unlikely to be replicated in Asia.